2019
DOI: 10.3390/ijms20122892
|View full text |Cite
|
Sign up to set email alerts
|

Y Chromosome, Hypertension and Cardiovascular Disease: Is Inflammation the Answer?

Abstract: It is now becomingly increasingly evident that the functions of the mammalian Y chromosome are not circumscribed to the induction of male sex. While animal studies have shown variations in the Y are strongly accountable for blood pressure (BP), this is yet to be confirmed in humans. We have recently shown modulation of adaptive immunity to be a significant mechanism underpinning Y-chromosome-dependent differences in BP in consomic strains. This is paralleled by studies in man showing Y chromosome haplogroup is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 79 publications
0
18
0
2
Order By: Relevance
“…A higher occurrence of cardiovascular diseases in males is also a well-known phenomenon. 42 Our cohort is characterized by a remarkable predominance of locally advanced tumors: pT3 carcinoma represented 49.6% [45.4-53.7] and pT4 35.6% [31.7-39.7], but pT2 only 11.9% [9.5-14.9] of all cases. In parallel with this, we observed a high rate of perineural and lymphatic invasion, in contrast to previous studies in other countries.…”
Section: Discussionmentioning
confidence: 89%
“…A higher occurrence of cardiovascular diseases in males is also a well-known phenomenon. 42 Our cohort is characterized by a remarkable predominance of locally advanced tumors: pT3 carcinoma represented 49.6% [45.4-53.7] and pT4 35.6% [31.7-39.7], but pT2 only 11.9% [9.5-14.9] of all cases. In parallel with this, we observed a high rate of perineural and lymphatic invasion, in contrast to previous studies in other countries.…”
Section: Discussionmentioning
confidence: 89%
“…78 Although the biological basis for these sex-related differences in hypertension remain unclear, sex hormones, Y chromosome, Ang II, aldosterone, and sex hormoneerelated signalling play a critical role. [79][80][81] In addition, growing evidence suggests that oxidative stress may be important in the sexual dimorphism in hypertension. 82 Both clinical and preclinical studies have demonstrated that biomarkers of oxidative stress are higher in men than in women.…”
Section: Oxidative Stress Sex and Hypertensionmentioning
confidence: 99%
“…Although the mechanism by which the Y chromosome influences heterochromatin/ euchromatin content and thus the transcription of the other genes is largely unknown, one of the hypotheses postulates that the Y chromosome sequesters heterochromatinization factors and another that it affects the architecture of cell nucleus, which makes specific genes inaccessible to the transcription factors [19][20][21][22]. Phylogenetic studies showed that the males with the haplogroup I, which is one of the most popular European lineages of the Y chromosome, have upregulated inflammatory response, downregulated adaptive immunity, and a higher risk of coronary diseases [23][24][25]. In the murine models, Y chromosomes influence the number of natural killer T cells, the gene expression pattern in CD4 + T cells, the immune response of macrophages, and the mortality rate following the infection with coxsackievirus [26][27][28], which argues for the strong impact of the Y chromosome on a large variety of immune cells and immune processes.…”
Section: Y Chromosomementioning
confidence: 99%